Study of Machining Strategies for CNC Milling of Foot Prosthetic Using Taguchi Methodology - Wahyu Dwi Lestari; Ndaru Adyono; Ahmad Khairul Faizin; Kadek Heri Sanjaya (TEKNIK, 2023)
The use of CNC milling machines in the industrial sector greatly contributes to the production of high-quality products that align with consumers' desired shapes. Currently, the precise machining parameters for manufacturing a product are determined through a time-consuming and costly process of trial and error. Most prior significant studies have examined the variables that can impact the duration of machining time. However, different machining conditions require different control factors. The key objective of this study is to enhance the machining parameters and identify the crucial factors that influence the duration of machining in the production of foot prostheses. The experiment was conducted using a 3-axis CNC milling machine with five machine parameters: spindle speed, feed rate, step over, depth of cut, and toolpath strategy. The Taguchi method with orthogonal array L2735 was chosen as an optimization method. The optimum machine parameters are analyzed using signal-to-noise (S/N) ratio and ANOVA. The analysis shows that spindle speed is the most influential variable on machine time. The next factor is the depth of cut, feed rate, and toolpath strategy, and the last is step over.